Photosynthetic Bradyrhizobia from Aeschynomene spp. Are Specific to Stem-Nodulated Species and Form a Separate 16S Ribosomal DNA Restriction Fragment Length Polymorphism Group - Molouba, Flore (American Society for Microbiology, 1999)
We obtained nine bacterial isolates from root or collar nodules of the non-stem-nodulated Aeschynomene species A. elaphroxylon, A. uniflora, or A. schimperi and 69 root or stem nodule isolates from the stem-nodulated Aeschynomene species A. afraspera, A. ciliata, A. indica, A. nilotica, A. sensitiva, and A. tambacoundensis from various places in Senegal. These isolates, together with 45 previous isolates from various Aeschynomene species, were studied for host-specific nodulation within the genus Aeschynomene, also revisiting cross-inoculation groups described previously by D. Alazard (Appl. Environ. Microbiol. 50:732–734, 1985). The whole collection of Aeschynomene nodule isolates was screened for synthesis of photosynthetic pigments by spectrometry, high-pressure liquid chromatography, and thin-layer chromatography analyses. The presence of puf genes in photosynthetic Aeschynomene isolates was evidenced both by Southern hybridization with a Rhodobacter capsulatus photosynthetic gene probe and by DNA amplification with primers defined from photosynthetic genes. In addition, amplified 16S ribosomal DNA restriction analysis was performed on 45 Aeschynomene isolates, including strain BTAi1, and 19 reference strains from Bradyrhizobium japonicum, Bradyrhizobium elkanii, and other Bradyrhizobium sp. strains of uncertain taxonomic positions. The 16S rRNA gene sequence of the photosynthetic strain ORS278 (LMG 12187) was determined and compared to sequences from databases. Our main conclusion is that photosynthetic Aeschynomene nodule isolates share the ability to nodulate particular stem-nodulated species and form a separate subbranch on the Bradyrhizobium rRNA lineage, distinct from B. japonicum and B. elkanii.